2018
DOI: 10.1111/pcn.12633
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anxious temperament and harm avoidance in medical students and staff

Abstract: These findings support our hypothesis and suggest that anxious temperament may have 'depressive proneness' whereas harm avoidance may have 'passive proneness.'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Previous studies have suggested that the personality tendency to avoid danger is related to the likeliness of an individual to become anxious and depressed [17,18]. Interestingly, Qian and Yahara have suggested that personality tendencies, morality and ideology are associated with SRB during COVID-19 pandemic in Japan [19].…”
Section: Introduction Backgroundmentioning
confidence: 94%
“…Previous studies have suggested that the personality tendency to avoid danger is related to the likeliness of an individual to become anxious and depressed [17,18]. Interestingly, Qian and Yahara have suggested that personality tendencies, morality and ideology are associated with SRB during COVID-19 pandemic in Japan [19].…”
Section: Introduction Backgroundmentioning
confidence: 94%
“…In addition, psychiatric diagnostic interviews based on the DSM‐5/ICD‐11 should be conducted due to high comorbidity of psychiatric disorders, and those under the threshold levels should also be evaluated. Psychometrics, especially to grasp personality, attachment, and Internet addiction tendency, are recommended . To assess behavioral characteristics, economic games, especially trust games, can evaluate unconscious decision‐making and consequently estimate interpersonal relationships .…”
Section: Therapeutic Approaches For Hikikomorimentioning
confidence: 99%
“…Psychometrics, especially to grasp personality, attachment, and Internet addiction tendency, are recommended. [121][122][123][124][125] To assess behavioral characteristics, economic games, especially trust games, can evaluate unconscious decision-making and consequently estimate interpersonal relationships. 126 Biological assessments, including blood tests, and brain functional analysis, such as electroencephalography, may help to understand the biological bases of hikikomori.…”
Section: Home Visitsmentioning
confidence: 99%
“…Using a database of 111 healthy volunteers, we have already shown that Anxious Temperament scores rated using the TEMPS‐A and Harm Avoidance scores rated using the TCI were significantly and positively associated with each other after adjustment of relevant factors using multiple regression analyses, and that anxious temperament may be associated with ‘depressive proneness’ whereas harm avoidance may be associated with ‘passive proneness.’…”
mentioning
confidence: 99%
“…Using a database of 111 healthy volunteers, we have already shown that Anxious Temperament scores rated using the TEMPS-A and Harm Avoidance scores rated using the TCI were significantly and positively associated with each other after adjustment of relevant factors using multiple regression analyses, and that anxious temperament may be associated with 'depressive proneness' whereas harm avoidance may be associated with 'passive proneness.' 3 Another intriguing association is that between hyperthymic temperament and self-directedness and/or self-transcendence. Hyperthymic temperament is characterized by terms such as 'cheerful,' 'overoptimistic, ' 'overtalkative,' 'warm,' 'people-seeking,' 'extroverted,' 'overconfident,' 'self-assured,' and 'high energy level.'…”
mentioning
confidence: 99%